2009
DOI: 10.1002/ird.524
|View full text |Cite
|
Sign up to set email alerts
|

Salinity patterns in irrigation systems, a threat to be demystified, a constraint to be managed: Field evidence from Algeria and Tunisia

Abstract: Salinity problems induced by irrigation are often presented in the literature as a threat that can only be managed at the irrigation scheme scale by installing subsurface drainage. On the other hand, salinity is a constraint that has often been successfully managed locally by farmers adapting their practices. However, the continuing expansion of irrigation with related water scarcity problems plus the increasing use of groundwater of marginal quality has resulted in a new challenge that is difficult to handle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…In North Africa, Bouarfa et al . () and Ghazouani et al . () showed that farmers are able to mitigate the effect of salinity on agricultural production through a host of appropriate agricultural practices.…”
Section: Groundwater: From Nuisance To (Contested) Fortunementioning
confidence: 89%
See 2 more Smart Citations
“…In North Africa, Bouarfa et al . () and Ghazouani et al . () showed that farmers are able to mitigate the effect of salinity on agricultural production through a host of appropriate agricultural practices.…”
Section: Groundwater: From Nuisance To (Contested) Fortunementioning
confidence: 89%
“…However, the drainage community should place drainage issues in the new context of irrigated agriculture, in which farmers are the main actors of the drainage processes due to their massive use of individual tubewells and in which techniques that save irrigation water are spreading rapidly. In such a context, waterlogging is no longer a fatality and farmers generally adapt their practices to deal with salinity (Bouarfa et al , ). In Figure , we provocatively assume that the general trend of a groundwater level is towards a decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt is a result of the high evaporation rate characterising arid and semiarid climates, an effect that causes salt to accumulate in the top layer of the soil (Al-Amoud, 2010). It can also come from irrigation with marginal groundwater resources and from a rise in the water table (Bouarfa et al, 2009).…”
Section: Differences In Weed Composition Between Crop Typesmentioning
confidence: 99%
“…While palm tree plantations used to be well-drained, there is now a lack of maintenance of drainage systems, which combined with the water table rise, makes soils wetter. Also, the water from the water table is increasingly salty and salt gradually accumulates in the soil over time (Bouarfa et al, 2009). Therefore, with time, weed flora characterising humid and salty soils and consisting of such species as C. cretica, C. rotundus and P. australis has colonised the area.…”
Section: Changes In Weed Composition Over Timementioning
confidence: 99%